The immune cell infiltrate in the tumour microenvironment of phaeochromocytomas and paragangliomas. Issue 11 (19th September 2022) - Tufton, N; Hearnden, R J; Berney, D M; Drake, W M; Parvanta, L; Chapple, J P; Akker, S A
Abstract : Emerging evidence suggests the composition of the tumour microenvironment (TME) correlates with clinical outcome and that each tumour type has a unique TME including a variable population of inflammatory cells. We performed immunohistochemistry on 65 phaeochromocytoma and paraganglioma (PPGL) tumour samples with 20 normal adrenal medulla samples for comparison. The immune cells assessed were macrophages, lymphocytes and neutrophils, and we compared the proportion of infiltration of these immune cells with clinical and histopathological factors. There was a higher proportion of immune cells in tumour tissue compared to non-neoplastic adrenal medulla tissue, with a predominance of macrophages. There was a higher proportion of M2:M1 macrophages and T-helper lymphocytes in aggressive tumours compared to indolent ones. For SDHB -associated tumours, there was a higher proportion of M2 macrophage infiltration, with higher M2:M1 in aggressive SDHB PPGLs compared to indolent tumours. These data demonstrate that immune cells do infiltrate the TME of PPGLs, confirming that PPGLs are immunologically active tumours. Differences in the TME of PPGLs were observed between aggressive and indolent tumours. These differences could potentially be exploited as an aid in predicting tumour behaviour.